Pro/con debate: Is etomidate safe in hemodynamically unstable critically ill patients? - Flynn, Gordon (BioMed Central, 2012)
Etomidate is an induction agent known for its smooth intubating conditions and cardiovascular stability. Studies, however, have shown that a single dose of etomidate can result in a prolonged adrenal insufficiency. The impact of this in patients with sepsis has been a matter for debate. This review presents a pro/con case for using etomidate in hemodynamically unstable critically ill patients and provides guidance for alternative induction techniques and when the use of etomidate might be justified despite these concerns.